American modernism (1910-1945) - Lathbury, Roger (New York, NY : Facts On File, 2006)
"Explores the social, cultural, and historical contexts of American literature from 1910 to 1945"--P. [4] of cover.
American modernism -- The lost generation -- Modernism in the American novel : Joyce, Dos Passos, and Faulkner -- The Harlem Renaissance (1919-1929) -- Modernism in poetry and drama -- Literary culture of the moderns -- Timeline.
Includes bibliographical references (p. 94) and index.
Keywords: American literature -- 20th century -- History and criticism; Modernism (Literature) -- United States